Survey of extension radio programs in Vigo County, Indiana - Brown, Charles Leland, author; Bicknell, J. E., advisor; Miller, Carroll H. (Carroll Hiram), 1907-, committee member; McClanahan, Walter R., committee member; Wetzel, Clarence Ludwig, committee member; Bicknell, John E., committee member (Colorado State University. Libraries, 1949)
To view the abstract, please see the full text of the document.
Covers not scanned.
Keywords: Agricultural extension work; Radio in education; Radio audiences -- Indiana -- Vigo County